INDIAN CINEMA TODAY AND TOMORROW infrastructure, aesthetics, audiences. - Srinivas, S. V.; Radhakrishnan, Ratheesh; Chatterjee, Subhajit; Omita, Goyal ([S.l.] : ROUTLEDGE, 2024)
Cinema has been, and is, a powerful tool for social mobilisation. The political importance of cinema was of course always well-known and has continued to evolve and grow. However, with innovations in modern technology, there has been the exponential growth of television alongside the movies, with content made especially for TV, as well as social media. This volume covers developments in Indian Cinema over the last decade. It explores an array of changes which has dramatically changed cinema -- a surge of new filming and broadcasting technologies, from the camera phone to the most sophisticated digital equipment; an avalanche of talent, from trained to completely untrained actors; and a volume of content difficult to document and categorise. It also studies cinema growth and reactions to the onslaught of home entertainment and discusses its changing formats over the years, from TV to satellite, to VCRs and DVDs, serials to OTT streaming platforms. This book will be of great interest to scholars and researchers in film studies, performance studies, cultural studies, media studies, and popular culture. It will also interest professionals working in media and entertainment industries.
Keywords: Motion pictures -- India; Motion pictures -- Social aspects -- India; PERFORMING ARTS / Film & Video / General; SOCIAL SCIENCE / Media Studies; SOCIAL SCIENCE / Popular Culture